(untitled) (Global Journal of Science Frontier Research, 2015)
This study demonstrates the adaptation of Unified Theory of acceptance and use of technology (UTAUT) to examine the factors that influence the intention to use internet marketing. This is a comparative study which compares the findings from the studies in Delhi and Chandigarh. This study is carried out by a self-administered questionnaire designed using established scales Statistical Package for the Social Sciences (SPSS) and Partial Least Square (PLS) were used to analyse the data.